Alih Kode dan Campur Kode Dialog Tutur Sepuh di Semarang Tv Edisi Januari-November 2019 (Sutasoma : Jurnal Sastra Jawa, 2022)
The purpose of this study is to describe the types of code switching that occur in the Speech Sepuh dialogue on Semarang TV January November 2019 edition and describe the form of code mixing in the form of words, phrases, baster, word repetition, clauses obtained in the Sepuh Speech dialogue on Semarang TV January edition. November 2019. The research method is descriptive qualitative. The data source for this research is video documents from youtube, the Tutur Sepuh event on Semarang TV in January November 2019. The data collection technique was obtained by the listening method followed by the note-taking technique. The data analysis technique uses the comparative method or also called the equivalent method. The results of the study were in the form of code switching from Javanese to Indonesian, forms of code mixing in Javanese with Indonesian, Javanese with Arabic, and several factors were found behind the occurrence of code switching and code mixing, namely the limitations of the use of codes, the use of more popular terms. , variety and level of speech. Keywords: Code switching, Code mixing Tutur Sepuh